Clinical competencies of nurses and forms of postgraduate education - Sabina Katarzyna Stadnicka; Magdalena Kowal; Alina Trojanowska; Danuta Zarzycka (Kazimierz Wielki University, 2018)
Introduction Over the last few years, the health care system has been transforming. The qualifications of medical staff are systematically improving due to the increasing pressure to raise the level of competence in line with the development of medicine and the expectations of healthcare recipients. Aim The aim of the study is the comparison of the clinical competence of the nurses whilst taking into the account the forms of postgraduate education. Material and research methods The study included 120 nurses aged 24-53 years, working in paediatric wards in Antoni Gębala University Hospital for Children in Lublin. The research tool was a questionnaire Belimage which contains 38 questions covering five areas: demographics, competence, nursing care, teamwork and care environment. Results The research demonstrates that the professional competence level of the respondents was the most significantly influenced by: practical experience and own reflections (85.00%), introduction in the current workplace (52.50%), sharing competence and experience with colleagues-nurses (tutorial guidance, working meetings, conversations) (51.67%). In the surveyed group, 100% of the respondents claimed that it was necessary to invest in various fields in order to optimize the level of nursing competence. The nurses who completed a specialization (43.48%) and higher education (79.17%) also evaluated the quality of care as excellent. Instrumental and technical competencies (4.50), as well as social and communication skills (4.20) are important for the nurses with Master's degree. Conclusions It has been proven that practical experience and own perspectives have the biggest influence on the respondents' professional competence level. Investing in various forms of postgraduate education and training, such as specialist courses and training, and university education, will optimize the level of nursing proficiency. Education, work experience and the time elapsed since graduation do not affect the assessment of the level of respondents' competence. The survey participants with higher education, specialization and certificates of completed training, felt slightly more often that the quality of patient care on the ward is excellent.